2020
DOI: 10.1038/s41586-020-2633-x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the C9orf72 ARF GAP complex that is haploinsufficient in ALS and FTD

Abstract: Mutation of C9ORF72 is the most prevalent defect in amyotrophic lateral sclerosis (ALS) and frontal temporal degeneration (FTD). Together with hexanucleotide repeat expansion, haploinsufficiency of C9ORF72 contributes to neuronal dysfunction. We determined the structure of the SMCR8-C9orf72-WDR41 complex by cryo-EM. C9orf72 and SMCR8 are both longin-DENN domain proteins, while WDR41 is a beta-propeller protein that binds to SMCR8 such that the whole structure resembles an eye slip hook. Contacts between WDR41 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 66 publications
(125 reference statements)
8
63
0
Order By: Relevance
“…Both C9orf72 and its cellular binding partner SMCR8 are longin and DENN domain (differentially expressed in normal and neoplastic cells) containing proteins 19 . Two cryo-electron microscopy structural studies of the C9orf72:SMCR8:WDR41 complex found that SMCR8 is sandwiched between C9orf72 and WDR41 20,21 . Structural similarity was observed between C9orf72:SMCR8 and another double longin-DENN complex, the folliculin and folliculin-interacting protein 2 (FLCN-FNIP2) complex 22,23 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both C9orf72 and its cellular binding partner SMCR8 are longin and DENN domain (differentially expressed in normal and neoplastic cells) containing proteins 19 . Two cryo-electron microscopy structural studies of the C9orf72:SMCR8:WDR41 complex found that SMCR8 is sandwiched between C9orf72 and WDR41 20,21 . Structural similarity was observed between C9orf72:SMCR8 and another double longin-DENN complex, the folliculin and folliculin-interacting protein 2 (FLCN-FNIP2) complex 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…FLCN-FNIP2 is a GTPase activating protein (GAP) complex for RagC in the mTORC1 signaling pathway, with the putative catalytic Arg residue residing in the FLCN subunit. This suggested that C9orf72:SMCR8 might also be a GAP for some small GTPase 20,21 . The C9orf72 complex was reported to have GAP activity for both ARF family proteins 21 , and the RAB proteins RAB8A and RAB11A 20 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that Ice2p is a distant homologue of SERINCs, another family of integral membrane proteins of unknown function, which are distributed across all eukaryotes, often with multiple members per species (for example, five in humans). The Ice2p-SERINC homology is stronger than many homologies identified by HHpred that subsequently have been confirmed by structural studies (Mariani et al, 2011;Schauder et al, 2014;Su et al, 2020). Additional factors cement the Ice2/SERINC homology: overall topologies are identical ( Figure 2); sequence similarities stretch the whole length ( Figure S4); key residues for SERINC function are among those conserved in Ice2p ( Figure 5B).…”
Section: Ice2p Is a Member Of The Serinc Superfamilymentioning
confidence: 74%